IMiDs mobilize acute myeloid leukemia blasts to peripheral blood through downregulation of CXCR4 but fail to potentiate AraC/Idarubicin activity in preclinical models of non del5q/5q- AML. (2nd September 2018) - Lopez-Millan, Belen; Diaz de la Guardia, Rafael; Roca-Ho, Heleia; Anguita, Eduardo; Islam, Abul B. M. M. K.; Romero-Moya, Damia; Prieto, Cristina; Gutierrez-Agüera, Francisco; Bejarano-Garcia, Jose Antonio; Perez-Simon, Jose Antonio; Costales, Paula; Rovira, Montse; et al.
ABSTRACT: Treatment for acute myeloid leukemia (AML) remains suboptimal and many patients remain refractory or relapse upon standard chemotherapy based on nucleoside analogs plus anthracyclines. The crosstalk between AML cells and the BM stroma is a major mechanism underlying therapy resistance in AML. Lenalidomide and pomalidomide, a new generation immunomodulatory drugs (IMiDs), possess pleiotropic anti-leukemic properties including potent immune-modulating effects and are commonly used in hematological malignances associated with intrinsic dysfunctional BM such as myelodysplastic syndromes and multiple myeloma. Whether IMiDs may improve the efficacy of current standard treatment in AML remains understudied. Here, we have exploited in vitro and in vivo preclinical AML models to analyze whether IMiDs potentiate the efficacy of AraC/Idarubicin-based standard AML chemotherapy by interfering with the BM stroma-mediated chemoresistance. We report that IMiDs do not exert cytotoxic effects on either non-del5q/5q- AML cells nor BM-MSCs, but they enhance the immunomodulatory properties of BM-MSCs. When combined with AraC/Idarubicin, IMiDs fail to circumvent BM stroma-mediated resistance of non-del5q/5q- AML cells in vitro and in vivo but induce robust extramedullary mobilization of AML cells. When administered as a single agent, lenalidomide specifically mobilizes non-del5q/5q- AML cells, but not healthy CD34 + cells, to peripheral blood (PB) through specific downregulation of CXCR4 in AML blasts. Global gene expression profiling supports a migratory/mobilization gene signature in lenalidomide-treated non-del5q/5q- AML blasts but not in CD34 + cells. Collectively, IMiDs mobilize non-del5q/5q- AML blasts to PB through CXCR4 downregulation, but fail to potentiate AraC/Idarubicin activity in preclinical models of non-del5q/5q- AML.